Systemic Risk and Optimal Regulatory Architecture - Espinosa-Vega, Marco (IMF Working Papers; Working Paper ;, 2011)
Until the recent financial crisis, the safety and soundness of financial institutions was assessed from the perspective of the individual institution. The financial crisis highlighted the need to take systemic externalities seriously when rethinking prudential oversight and the regulatory architecture. Current financial reform legislation worldwide reflects this intent. However, these reforms have overlooked the need to also consider regulatory agencies' forbearance and information sharing incentives. In a political economy model that explicitly accounts for systemic connectedness, and regulators' incentives, we show that under an expanded mandate to explicitly oversee systemic risk, regulators would be more forbearing towards systemically important institutions. We also show that when some regulators have access to information regarding an institutions' degree of systemic importance, these regulators may have little incentive to gather and share it with other regulators. These findings suggest that (and we show conditions under which) a unified regulatory arrangement can reduce the degree of systemic risk vis-a-vis a multiple regulatory arrangement.